A loss of function mutation in the filaggrin gene associated with ichthyosis vulgaris and rheumatoid arthritis. (2nd August 2021) - Xu, Xinxin; Ma, Qingqing; Lin, Mu; Liu, Mubo; Huang, Chaolin; Ying, Jianchao; Ye, Jun
Introduction: Mutations in the filaggrin ( FLG ) gene are known to cause ichthyosis vulgaris. Methods: We used whole-genome sequencing (WGS) technology to investigate the genetic causes of rare and complex inherited diseases including rheumatoid arthritis, ichthyosis, and congenital fibrosis of the extraocular muscles type 1 (CFEOM1) in a Chinese family. WGS was performed in four topics, and the identified candidate mutations were further verified through Sanger sequencing. Results: We identified a mutation in FLG gene (g.152280098 C>A, p.E2422∗) that may be associated with ichthyosis and arthritis. Moreover, a mutation in KIF21A (g.39726207 G>A, p.R954 W) was also determined in affected members as the cause of CFEOM1. The gene interaction network demonstrated an interesting correlation between FLG and genes associated with arthritis and ichthyosis. Functional enrichment analysis of these interacting genes revealed several possible pathways that might be linked to arthritis and ichthyosis. Conclusion: In general, we confirmed a loss of function mutation in the FLG gene associated with ichthyosis vulgaris and rheumatoid arthritis in this family.